Palinofagia de los murcielagos del genero Glossophaga (Mammalia: Chiroptera) en México - Sánchez Casas, Nansy; Alvarez, Ticul (Instituto de Ecología, A.C., 2000)
The work is based upon the study of 1012 stomach contents of the four species of the genus Glossophaga (Mammalia:Phyllostomidae) living in Mexico. The contents of each stomach were analyzed both quantitative and qualitatively. Pollen from thirty six species was identified, mostly from Mastichodendron capiri, Crescentia alata, Pseudobombax ellipticum, Cordia alliodora, Pithecellobium lanceolatum, Ipomoea sp. and Bursera sp. To evaluate differences in feeding habits, we separated specimens by sex, season and locality. We found significant sexual, seasonal, and geographic differences. Glossophaga soricina was the species with highest number of pollen species identified in its digestive tract. G. soricina is the most widely distributed species in the genus in Mexico and we considered it also the most opportunistic. When the feeding habits of different species were compared, we found some overlapping in the diet that not necessarily indicates common use of resources.